2019
DOI: 10.5089/9781498313087.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Export Diversification: Key Drivers and Policy Implications

Abstract: We identify key factors, from large set of potential determinants, that explain the variation in export diversification across countries and over time using Bayesian Model Averaging (BMA), which addresses model uncertainty and ranks factors in order of importance vis-avis their explanatory power. Our analysis suggests, in order to diversify, policy makers should prioritize human capital accumulation and reduce barriers to trade. Other policy areas include improving quality of institutions and developing the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 15 publications
8
30
3
2
Order By: Relevance
“…This may explain "the reduced importance of the country in global value chains" (López et al, 2015, p.32). Further, Colombia's notable dependence on the performance of the oil sector (see Garavito-Acosta et al, 2020) exposed the country to volatility shocks (see Giri, Quayyum, & Yin, 2019).…”
Section: Colombian Regional and International Trade Policies During Tmentioning
confidence: 99%
“…This may explain "the reduced importance of the country in global value chains" (López et al, 2015, p.32). Further, Colombia's notable dependence on the performance of the oil sector (see Garavito-Acosta et al, 2020) exposed the country to volatility shocks (see Giri, Quayyum, & Yin, 2019).…”
Section: Colombian Regional and International Trade Policies During Tmentioning
confidence: 99%
“…Hybrid regime refers to an application of both concession-based and production-sharing or service contracts. Source: Author's elaboration based on information from (EY, 2018 [6]). Note: Resource-rich countries are those that raise 20% or more of government revenue from fossil-fuel resources.…”
Section: The Role Of Fossil Fuels In Government Budgetsmentioning
confidence: 99%
“…5 Revenue either from a contract-based or concession-based scheme can be generated from taxes levied on a firm's profitable endeavours and revenue raised from ownership, quasi-corporate functions, or through services (EITI, 2017 [7]). 6 More specifically, taxes are often collected from company profits, rents, the sale of goods and services, and export revenues; fees and royalties are charged either on production volumes or their market value. 7 Each instrument leads to behavioural responses throughout the life cycle of the project, affecting exploration and development efforts, production trajectories, and government take.…”
Section: The Role Of Fossil Fuels In Government Budgetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the variable RENT, which captures the abundance in natural resources in a given country, has been included in model (1) because some studies (e.g. Alsharif, ; Giri, Quayyum, & Yin, ) have shown that high dependency on natural resources impedes export product diversification. Therefore, a greater level of dependence on natural resources is expected to be associated with a higher degree of export product concentration.…”
Section: Empirical Strategymentioning
confidence: 99%